1995
DOI: 10.1111/j.1365-2249.1995.tb03778.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunological markers indicating the effectiveness of pharmacological treatment in human hydatid disease

Abstract: SUMMARY The relation of interferon‐gamma (IFN‐γ), IL‐4, IL‐10 production and specific IgE, total IgG, IgG subclass expression to the effectiveness of pharmacological treatment in human hydatid disease (Echinococcus granulosus infection) was evaluated in 27 hydatid patients divided into four clinical groups according to their response to albendazole/mebendazole therapy (full, partial, low and non‐responders). After parasite antigen stimulation, peripheral blood mononuclear cells (PBMC) from full responders prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
53
0
8

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(68 citation statements)
references
References 21 publications
7
53
0
8
Order By: Relevance
“…It is noteworthy that the increased production of IL-4 and IL-10 in hydatid patients (Bayraktar et al, 2005) corresponds with high levels of IgE and IgG4 (Rigano et al, 1995b), suggesting regulation by IL-4 of IgE and IgG4 responses (Rigano et al, 2001;Rigano et al, 1995b;King and Nutman, 1993). Patients with a primary infection have higher levels of IL-2, IFN-γ and IL-5.…”
Section: Correlation Of Cytokines With Antibody Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy that the increased production of IL-4 and IL-10 in hydatid patients (Bayraktar et al, 2005) corresponds with high levels of IgE and IgG4 (Rigano et al, 1995b), suggesting regulation by IL-4 of IgE and IgG4 responses (Rigano et al, 2001;Rigano et al, 1995b;King and Nutman, 1993). Patients with a primary infection have higher levels of IL-2, IFN-γ and IL-5.…”
Section: Correlation Of Cytokines With Antibody Productionmentioning
confidence: 99%
“…T-cell lines from a patient with an inactive cyst had a Th1 profile, while T-cell lines derived from patients with active and transitional hydatid cysts had mixed Th1/Th2 and Th0 clones , indicating that Th1 lymphocytes contribute significantly to the inactive stage of hydatid disease, with Th2 lymphocytes being more important in the active and transitional stages. When CE patients were drug-treated with albendazole/mebendazole, a Th1 cytokine profile, rather than a Th2 profile, typically dominated, indicating that Th1 responses have a role in the process of cyst degeneration (Rigano et al, 1995b). An increased Th1-type cytokine IFN-γ response has been suggested as a marker for monitoring AE patient treatment (Dvoroznakova et al, 2004), whereas as measurement of serum IL-4 may be a useful marker for the follow up of patients with CE (Rigano et al, 1999b).…”
Section: T Cell Responses and Treatmentmentioning
confidence: 99%
“…In patients undergoing successful removal of hydatid cyst, the IgG4 subclass becomes negative soon after surgery and those with relapsing disease maintain high IgG4 titres on ELSIA. This suggests that IgG4 subclass is a good marker for hydatidosis follow-up [10].…”
Section: Discussionmentioning
confidence: 86%
“…Regarding the role of IL4 in hydatid cyst infection, it has been shown that in peripheral blood mononuclear from hydatid cyst patients stimulated with this parasite antigens, IL4 increased significantly (Rigano et al 1995a). Also a high level of IL4 has been reported in patients with chronic hydatid cyst (Rigano et al 1995b;Zhang et al 2003;Rigano et al 1996) Fibrous layer develops by host as a protective response to hydatid cyst. Expression of high level of IL4 in fibrous layer shows that this cytokine may play a key function in regulation of immune response in favor or against the parasite.…”
Section: Discussionmentioning
confidence: 99%